TRADISI SUMPAH BABISIAK MENURUT HUKUM ISLAM (Studi Kasus Di Nagari Lunto Kecamatan Lembah Segar Kota Sawahlunto) - Rahmi Sukma; Nailur Rahmi (Institut Agama Islam Negeri Batusangkar, 2023)
The main problem in this thesis is how the provisions of the tradition of prohibiting marriage due to babisiak vows in Nagari Lunto, Lembah Segar District, Sawahlunto City and how Islamic Law reviews Islamic law regarding the tradition of prohibiting marriage due to the babisiak oath. The purpose of this discussion is to find out and explain how the provisions of the tradition of prohibiting marriage due to babisiak vows and to find out an overview of Islamic law on the tradition of prohibiting marriage due to babisiak vows in Nagari Lunto, Lembah Segar District, Sawahlunto City. This type of research is field research. Data collection techniques are carried out through interviews and documentation is a process to obtain research data. The data sources for this research are the Chairperson of KAN Lunto, people who are dealing with the babisiak oath or people who currently hold the customary tradition of prohibiting marriage due to a babisiak oath, Niniak mamak 4 jinih, and the community in Nagari Lunto. The results of the research that the authors get, firstly that the provisions of the rules regarding the tradition of prohibiting marriage due to the Babisiak oath are customs that have been passed down from generation to generation which until now are still believed to exist by the people of Nagari Lunto, these rules are not written but are upheld by traditional leaders accompanied by sanctions and trusted there will be disaster and calamity for those who break it. Second, in Islamic Law the tradition of prohibiting marriage due to a babisiak oath is contrary to syara', because there is no text that says that prohibition on marriage such as the tradition of prohibiting marriage due to a babisiak oath is prohibited or forbidden, even those who wish to do marriage are not mahrams, for this it is customary regarding the tradition of prohibiting marriage due to the babisiak oath included in 'urf fasid.